(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2015)
Background: The current study on "Scope and Implementation of FSSAI Standards"- in free standing restaurants was done with the aim of studying the aspects of food safety in restaurants in Delhi NCR. Objective: The objective of the study was to find out the implementation of FSSAI standards by restaurants. Methods: Restaurants were selected through random sampling. Checklist was administered in order to find out the existing scenario of FSSAI standards. Result: It was observed that only 17% of the restaurants were following FSSAI Standards.